Floutage des frontières de genre : écrire des corps queers - Michaela Rumpíková (Svět Literatury)
The following article examines the process of gender/genre blurring through literary fiction. More specifically, it is concerned with textual poetics and bodily politics arising from the representation of queer and other-than-normative bodies. While these subjects have been historically controlled by normative discourses, mostly compared to monsters causing moral panic, the present narratives attempt to contest this ideological reality by what we could call “literary practice of boundary blurring”. This results in a distinct aesthetics where hybrid bodies and their discursive networks appear in various unexpected poetical ways and binary classifications become both troubled and troubling. Therefore, hybrid bodies and their discursive networks emerge in various unexpected poetical ways. In my analysis, critical attention is given to comparative dialogues between Monique Wittig & Léa Rivière and Virginia Woolf & Paul B. Preciado.